2017
DOI: 10.1002/anie.201707853
|View full text |Cite
|
Sign up to set email alerts
|

The Thermodynamic Basis of the Fuzzy Interaction of an Intrinsically Disordered Protein

Abstract: Many intrinsically disordered proteins (IDP) that fold upon binding retain conformational heterogeneity in IDP-target complexes. The thermodynamics of such fuzzy interactions is poorly understood. Herein we introduce a thermodynamic framework, based on analysis of ITC and CD spectroscopy data, that provides experimental descriptions of IDP association in terms of folding and binding contributions which can be predicted using sequence folding propensities and molecular modeling. We show how IDP can modulate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…This analysis demonstrates that even after binding, the interaction energetics are far from optimal in the fuzzy regions, in accord with experimental data. 16 Consistent with earlier results for individual cases, 32 we have found that both the disordered and structured regions of complexes are enriched in highly frustrated interactions in the bound complexes of disordered proteins. The interface contacts do decrease the frustration level in the disordered protein once bound as compared to the frustration of the free state, but the interactions often still remain suboptimal and energetic conflicts remain to be resolved ( Figures S3 and S4 ).…”
Section: Discussionsupporting
confidence: 90%
“…This analysis demonstrates that even after binding, the interaction energetics are far from optimal in the fuzzy regions, in accord with experimental data. 16 Consistent with earlier results for individual cases, 32 we have found that both the disordered and structured regions of complexes are enriched in highly frustrated interactions in the bound complexes of disordered proteins. The interface contacts do decrease the frustration level in the disordered protein once bound as compared to the frustration of the free state, but the interactions often still remain suboptimal and energetic conflicts remain to be resolved ( Figures S3 and S4 ).…”
Section: Discussionsupporting
confidence: 90%
“…A recent experimental example is the detailed study of the thermodynamics of the fuzzy complex between the C-terminal IDR of antitoxin CcdA, which adopts α helical structure at the time of binding the toxin dimer CcdB (HadŽi et al, 2017 ). The authors perform a series of mutations that affect contacting and non-contacting residues.…”
Section: Fuzzy Complexes and Multivalencymentioning
confidence: 99%
“…The critical element of the applied framework is to consider motif-interactions with multiple sites. Experimental and computational studies highlight that ID binding is largely influenced by non-native interactions [70][71][72]. Even in case of templated folding, non-native contacts frustrate the binding free energy landscape [73,74], and enable multiple bound configurations [75].…”
Section: Discussionmentioning
confidence: 99%